Conventional and novel cardiovascular risk factors in young Finns and their associations with structural and functional vascular changes of subclinical atherosclerosis. The Cardiovascular Risk in Young Finns Study - Raiko, Juho (Annales Universitatis Turkuensis D 981, 2011)
Background: Atherosclerosis begins in early life progressing from asymptomatic to symptomatic as we age. Although substantial progress has been made in identifying the determinants of atherosclerosis in middle to older age adults at increased cardiovascular risk, there is lack of data examining determinants and prediction of atherosclerosis in young adults. Aims: The current study was designed to investigate levels of cardiovascular risk factors in young adults, subclinical measures of atherosclerosis, and prediction of subclinical arterial changes with conventional risk factor measures and novel metabolic profiling of serum samples. Subjects and Methods: This thesis utilised data from the follow-ups performed in 2001 and 2007 in the Cardiovascular Risk in Young Finns study, a Finnish population-based prospective cohort study that examined 2,204 subjects who were aged 30-45 years in 2007. Subclinical atherosclerosis was studied using noninvasive ultrasound measurements of carotid intima-media thickness (IMT), carotid arterial distensibility (CDist) and brachial flow-mediated dilation (FMD). Measurements included conventional risk factors and metabolic profiling using highthroughput nuclear magnetic resonance (NMR) methods that provided data on 42 lipid markers and 16 circulating metabolites. Results: Trends in lipids were favourable between 2001 and 2007, whereas waist circumference, fasting glucose, and blood pressure levels increased. To study the stability of noninvasive ultrasound markers, 6-year tracking (the likelihood to maintain the original fractile over time) in 6 years was examined. IMT tracked more strongly than CDist and FMD. Cardiovascular risk scores (Framingham, SCORE, Finrisk, Reynolds and PROCAM) predicted subclinical atherosclerosis equally. Lipoprotein subclass testing did not improve the prediction of subclinical atherosclerosis over and above conventional risk factors. However, circulating metabolites improved risk stratification. Tyrosine and docosahexaenoic acid were found to be novel biomarkers of high IMT. Conclusions: Prediction of cardiovascular risk in young Finnish adults can be performed with any of the existing risk scores. The addition of metabonomics to risk stratification improves prediction of subclinical changes and enables more accurate targeting of prevention at an early stage.

Perinteiset ja uudet sydän- ja verisuonitautien riskitekijät nuorilla suomalaisilla ja niiden yhteydet rakenteellisiin ja toiminnallisiin varhaisiin ateroskleroottisiin valtimomuutoksiin. Lasten Sepelvaltimotaudin Riskitekijät -projekti. Tausta: Ateroskleroosin kehittyminen alkaa varhain ja kehittyy ikaantymisen myota oireettomasta sairaudesta oireelliseksi. Vaikka ateroskleroosin mittausmenetelmat ja kohonneessa sydan- ja verisuonitautiriskissa olevien keski-ikaisten ja vanhempien ihmisten tunnistaminen ovat kehittyneet huomattavasti, nuorten aikuisten sydan- ja verisuonitautiriskin maarittamista ja varhaisen ateroskleroosin ennustamista on tutkittu vain vahan. Tavoitteet: Tutkimuksessa selvitettiin sydan- ja verisuonitautien riskitekijoiden tasoja nuorilla aikuisilla, varhaisten ateroskleroottisten muutosten mittaamista ja varhaisten valtimomuutosten ennustamista perinteisilla riskitekijoilla ja uudella menetelmalla, seeruminaytteiden metabolisella profiloinnilla. Tutkimushenkilöt ja -menetelmät: Tutkimuksessa kaytettiin Lasten Sepelvaltimotaudin Riskitekijat –projektissa vuosina 2001 ja 2007 kerattyja mittaustuloksia 2204 aikuiselta, jotka vuonna 2007 olivat 30-45-vuotiaita. Varhaista ateroskleroosia tutkittiin noninvasiivisesti ultraaanella mittaamalla kaulavaltimon intima-media-paksuus (IMT) ja distensibiliteetti (CDist) ja olkavaltimon virtausvalitteinen laajeneminen (FMD). Lisaksi mitattiin perinteiset riskitekijat ja seeruminaytteiden metabolinen profiili, joka koostui 42 lipidimarkkerista ja 16 metaboliitista. Tulokset: Vuosien 2001 ja 2007 valilla lipiditasojen kehitys oli myonteista, mutta vyotaronymparys, paastoglukoosi ja verenpaine nousivat. IMT-mittaukset olivat stabiilimpia verrattuna CDist- ja FMD-mittauksiin. Sydan- ja verisuonitautiriskilaskurit (Framingham, SCORE, Finrisk, Reynolds ja PROCAM) ennustivat varhaista ateroskleroosia yhta tarkasti. Lipoproteiinien alaluokkien maarittaminen ei parantanut varhaisen ateroskleroosin ennustamista perinteisiin riskitekijoihin verrattuna, mutta metaboliittien maarittaminen paransi riskin arviointia. Tyrosiini ja dokosaheksaeenihappo olivat uusia korkean IMT:n biomarkkereita. Johtopäätökset: Varhaisen ateroskleroosin ennustamiseen nuorilla suomalaisilla voidaan kayttaa kaikkia nykyisia riskilaskureita. Metabolinen profilointi parantaa varhaisen ateroskleroosin riskin arviointia ja mahdollistaa varhaisen ja tarkan hoidon aloittamisen.